Comparison of atmospheric CO2 mole fractions and source–sink characteristics at four WMO/GAW stations in China. (May 2018) - Cheng, Siyang; Zhou, Lingxi; Tans, Pieter P.; An, Xingqin; Liu, Yunsong
Abstract: As CO2 is a primary driving factor of climate change, the mole fraction and source–sink characteristics of atmospheric CO2 over China are constantly inferred from multi-source and multi-site data. In this paper, we compared ground-based CO2 measurements with satellite retrievals and investigated the source–sink regional representativeness at China's four WMO/GAW stations. The results indicate that, firstly, atmospheric CO2 mole fractions from ground-based sampling measurement and Greenhouse Gases Observing Satellite (GOSAT) products reveal similar seasonal variation. The seasonal amplitude of the column-averaged CO2 mole fractions is smaller than that of the ground-based CO2 at all stations. The extrema of the seasonal cycle of ground-based and column CO2 mole fractions are basically synchronous except a slight phase delay at Lin'an (LAN) station. For the two-year average, the column CO2 is lower than ground-based CO2, and both of them reveal the lowest CO2 mole fraction at Waliguan (WLG) station. The lowest (∼4 ppm) and largest (∼8 ppm) differences between the column and ground-based CO2 appear at WLG and Longfengshan (LFS) stations, respectively. The CO2 mole fraction and its difference between GOSAT and ground-based measurement are smaller in summer than in winter. The differences of summer column CO2 among these stations are also much smaller than their ground-based counterparts. In winter, the maximum of ground-based CO2 mole fractions and the greatest difference between the two (ground-based and column) datasets appear at the LFS station. Secondly, the representative areas of the monthly CO2 background mole fractions at each station were found by employing footprints and emissions. Smaller representative areas appeared at Shangdianzi (SDZ) and LFS, whereas larger ones were seen at WLG and LAN. The representative areas in summer are larger than those in winter at WLG and SDZ, but the situation is opposite at LAN and LFS. The representative areas for the stations are different in summer and winter, distributed in four typical regions. The CO2 net fluxes in these representative areas show obvious seasonal cycles with similar trends but different varying ranges and different time of the strongest sink. The intensities and uncertainties of the CO2 fluxes are different at different stations in different months and source-sink sectors. Overall, the WLG station is almost a carbon sink, but the other three stations present stronger carbon sources for most of the year. These findings could be conducive to the application of multi-source CO2 data and the understanding of regional CO2 source–sink characteristics and patterns over China. Highlights: Multi-source CO2 mole fractions were compared at four typical stations in China. The representativeness of multi-station CO2 background mole fractions was studied. Representative areas of CO2 background concentrations were found at four stations. The CO2 source-sink characteristics in the representative areas were compared.